Insights from a minimal model of dislocation-assisted rafting in single crystal Nickel-based superalloys. (October 2016) - Wu, Ronghai; Sandfeld, Stefan
Abstract: Nickel-based superalloys play a major role in many technologically relevant high temperature applications. Understanding and predicting the evolution of the phase microstructure during high temperature creep together with the evolution of the dislocation microstructure is a challenge that up to date has not yet been fully accomplished. Our two-dimensional coupled phase-field/continuum dislocation dynamics model explains microstructural mechanisms which are important during the early stage of rafting in a single crystal system. It shows how γ / γ ′ phases and dislocations interact giving rise to realistic creep behavior; no phenomenological fit parameters are required. Graphical abstract: